IMPLEMENTATION OF HEALTH POLICY IN LAW NUMBER 36 OF 2009 REGARDING HEALTH SERVICES: A STUDY OF BPJS MATARAM CITY - Hidayat, Ramhat; Agustina, Nurillah; khairani, Suci; har, Ad; atunn, Ismi; Lestari, Aprilia Eka (Jurnal Paradigma, 2025)
The purpose of the BPJS Kesehatan program study on the implementation of health service policies in Mataram City based on Law Number 36 of 2009 is to evaluate the quality of services and identify success factors and challenges that arise. And using the theory of Van meter and Van Horn to measure the implementation of HEALTH POLICY IN LAW NUMBER 36 OF 2009 REGARDING HEALTH SERVICES: A STUDY OF BPJS MATARAM CITY. Collecting comprehensive information about the success of the services provided, this study uses qualitative techniques such as document analysis, key staff interviews, and field observations. With a high participation rate of 99%, the results of the study show how well BPJS, local governments, and health facilities collaborate to provide equitable health services to all levels of society. However, problems with service capacity and efficiency remain, therefore collaboration and periodic evaluation are needed. The conclusion of this study emphasizes the importance of resource allocation and community participation as well as stakeholders to improve service delivery and advance larger goals, namely health equity and social welfare in Mataram City. Periodic evaluations need to be carried out to produce results from BPJS.